The impact of crisis management strategies on organizational health: field study in the banking sector in Assiut Governorate - Sewify, Abeer Mokhtar (Journal of Risk and Crisis Management, 2021)
Organizational health is one of the administrative trends that focus on the organization ability to grow and develop in various work environments and interact with circumstance changes to achieve a better description than competitors. And in order to do this, there must be a system to manage various crisis that organizations may be exposed to, especially in the banking sector, which faces many crises in light of the rapid development in the work environment of this sector. Therefore, this research aims to identify the impact of crisis management strategies on organizational health in the banking sector in Assiut Governorate, and the research problem was represented in the following question: Do crisis management strategies affect organizational health in the banking sector in Assiut Governorate? The research relied on the descriptive analytical method, and the Pearson test was used to measure the correlation between the study variables and the dimensions of each of them. The research also used the regression coefficient to predict the relationship between the independent variable and the dependent variable of the study. The data was collected using a survey list prepared for the purpose of the study, and 286 lists were recovered at a rate of 74%. The study reached several results, the most important of which are: The degree of practicing of both crisis management and organizational health strategies came to a high degree, with the average value for each of them reaching 3.741 and 3.693in sequence. It was also found that there is a significant impact of all crisis management strategies on organizational health, and the research recommended the need to develop an integrated system for crisis management which is able to deal with crisis, in addition to the need to provide a supportive environment for organizational health.